[PP.19.10] ISOLATED SYSTOLIC HYPERTENSION CHARACTERISTICS: DATA FROM THE BRISIGHELLA HEART STUDY (ITALY) AND THE ENAH STUDY (CROATIA). (September 2016) - Parini, A.; Ivkovic, V.; Vrdoljak, A.; Baric, M. Abramovic; Bacchelli, S.; Cagnati, M.; Cicero, A.F.G.; Addato, S.D.; Esposti, D. degli; Fucek, M.; Grandi, E.; Ivandic, E.; et al.
Abstract : Objective: Isolated systolic hypertension (ISH) in elderly is associated with increased global risk. It could be considered as a rough biomarker of increased arterial stiffness and advanced biological aging. In our study, we evaluate the association between ISH and other cardio-metabolic risk factors in two rural European populations from South Europe (Italy and Croatia). Figure. No caption available. Design and method: In this international prospective long-term follow up study data on 5162 subjects from BrEnah cohort formed from original cohorts of Brisighella Heart Study (Italy) and ENAH Study (Croatia) were analized. Out of them 2253 subjects (694 from Croatia, 1559 from Italy; 980m, 1273f) were eligible for further analyses. BP was measured using Omron 6 device following the ESH guidelines. Fasting blood was analysed for glucose, lipids, uric acid, serum creatinine. Results: Results In general rural population from South Europe prevalence of ISH is high. Difference between Croatian and Italian subgroups was found (28.8% vs. 44.8%; p<0.001; no gender differences) what is concordance with difference in age between two cohorts. Beside age, ISH was significantly associated with eGFR and various metabolic parameters including visceral obesity glucose intolerance and uric acid Conclusions: In this group of patients prevalence of ISH was high. Observed difference between Italian and Croatian subgroup is mostly due to difference in age. Metabolic disturbances are frequently associated with ISH additionally increasing global risk.